A rhythm of prayer : a collection of meditations for renewal - Bessey, Sarah (Convergent, 2021)
"An antidote for our age of anxiety--thoughtful, moving prayers from Barbara Brown Taylor, Amena Brown, Nadia Bolz-Weber, and other artists, creatives, and thinkers, curated by the author Glennon Doyle calls 'my favorite faith writer.' It's no secret that we are overworked, overpressured, and edging burnout. Unsurprisingly, this fact is as old as time--and that's why we see so many prayer circles within a multitude of church traditions. These gatherings are a trusted space where people seek help, hope, and peace, energized by God and one another. This book, curated by acclaimed author Sarah Bessey, celebrates and honors that prayerful tradition in a literary form. A companion for daily inspiration, this collection gives women permission to recognize the weight of all they carry, while also offering a broadened imagination of hope--of what can be restored and made new. Each prayer is an original piece of writing, with a short introduction from Bessey sharing exactly why she loves and looks up to the writer. This book is a literary hug, an invitation for respite, and a chance for readers to pause and celebrate who they are, beyond what they do"--